2022
DOI: 10.1080/03054985.2022.2125371
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing interventions to promote equity in the early years: exploring the ‘impact’, legacy and lessons learned from a national evaluation of Children’s Centres in England

Abstract: This paper discusses the challenges facing a national evaluation of an early years intervention programme, Sure Start Children's Centres (SSCCs), that was implemented across England in the first decade of the 21st century. The paper describes the rationale for the evaluation's mixed methods research design and the ecological theoretical approach adopted. It investigates the SSCC policy aim of combatting the 'impact' of multiple disadvantage on outcomes for families, parents and children. Based on a clustered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A second study-the Evaluation of Children's Centres in England (ECCE)-run between 2011 and 2013 collected data from a subset of centres and related service use to child outcomes. The study found that more intensive service use was associated with an improved home learning environment, improved children's social behaviour and reduced parental distress (Sammons et al 2015). Focusing on health outcomes, and exploiting the full expansion of SSLPs and SSCCs, Cattan et al (2022) found that increased centre availability increased hospitalizations among young children (by 10% at age 1) and reduced hospitalizations at later ages (by 8-9% at ages 11-15).…”
Section: Conceptual Framework and Empirical Strategymentioning
confidence: 98%
See 1 more Smart Citation
“…A second study-the Evaluation of Children's Centres in England (ECCE)-run between 2011 and 2013 collected data from a subset of centres and related service use to child outcomes. The study found that more intensive service use was associated with an improved home learning environment, improved children's social behaviour and reduced parental distress (Sammons et al 2015). Focusing on health outcomes, and exploiting the full expansion of SSLPs and SSCCs, Cattan et al (2022) found that increased centre availability increased hospitalizations among young children (by 10% at age 1) and reduced hospitalizations at later ages (by 8-9% at ages 11-15).…”
Section: Conceptual Framework and Empirical Strategymentioning
confidence: 98%
“…The study found that more intensive service use was associated with an improved home learning environment, improved children's social behaviour and reduced parental distress (Sammons et al . 2015). Focusing on health outcomes, and exploiting the full expansion of SSLPs and SSCCs, Cattan et al .…”
Section: Conceptual Framework and Empirical Strategymentioning
confidence: 99%